Model Pembelajaran Kooperatif Tipe Jigsaw Meningkatkan Hasil Belajar - haerati haerati (IQRO: Journal of Islamic Education, 2019)
This research talk about model jigsaw on the subjects of moral all students viii modern class boarding datok Sulaiman the son of palopo , but the problem is basic: how the application of learning model type and cooperative jigsaw investigating whether the application of learning model cooperative type jigsaw can improve study results.The research is class action research but the data from the study is students viii modern class boarding datok Sulaiman the son of palopo when applied method of learning cooperative type jigsaw to obtain data researchers used technique observation and tests. Analysis of data conducted using qualitative analysis descriptive and quantitative. The research results show that using learning cooperative type jigsaw students study results any siklusnya changed significantly.Respectively the I and based on the study results moral ii is with subject matter believe in the books. I cycle is in the highest and the lowest 87 is 70. Ii cycle is in the highest and the lowest 95 is 80, average analysis procurement value the students in i am 80,14 II average in the procurement value increased by 88,32 students